2*-82+8=3*-82+90

Simple and best practice solution for 2*-82+8=3*-82+90 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2*-82+8=3*-82+90 equation:


Simplifying
2 * -82 + 8 = 3 * -82 + 90

Multiply 2 * -82
-164 + 8 = 3 * -82 + 90

Combine like terms: -164 + 8 = -156
-156 = 3 * -82 + 90

Multiply 3 * -82
-156 = -246 + 90

Combine like terms: -246 + 90 = -156
-156 = -156

Add '156' to each side of the equation.
-156 + 156 = -156 + 156

Combine like terms: -156 + 156 = 0
0 = -156 + 156

Combine like terms: -156 + 156 = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 27=12x+27 | | 2x+8=3x+90 | | 98+2= | | 4x*5+8=3x/8-13 | | x+14=2x | | 19/17=342/306 | | 19*18=17*18 | | 10+2/3x=6 | | 3x-14+2x+10=90 | | 9xn+6= | | 25=(39000-x)/y | | 6+6x-15+28+14x= | | -34-4= | | 41:9-?:9=4 | | 41:9-?:9=3 | | -1*-9=x | | 1/3x+3/4=11/8 | | (-5t/20)+18t/20 | | -7+z/8-2 | | X=99+357 | | 4a^2+20ab+25b^2=0 | | 2.8b-1.4b-6=1 | | 4(t-4)+8t=4(3t+3)-8 | | 4(2d-4)+6=6 | | 0.25=(39000-x)/y | | 7s-8=5s-13 | | 3x-4=3+x | | -6=x/-3-9 | | 6r+8-5=51 | | 13(p+3)=2p | | 1600=80x | | -4/5g=12 |

Equations solver categories